World statistics on mining and utilities 2018 - United Nations Industrial Development Organization; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
World Statistics on Mining and Utilities 2018 provides a unique biennial overview of the role of mining and utility activities in the world economy. This extensive resource from UNIDO provides detailed time series data on the level, structure and growth of international mining and utility activities by country and sector. Country level data is clearly presented on the number of establishments, employment and output of activities such as coal, iron ore and crude petroleum mining as well as the production and supply of electricity, natural gas and water. This unique and comprehensive source of information meets the growing demand of data users who require detailed and reliable statistical information on the primary industry and energy producing sectors. The publication provides internationally comparable data for economic researchers, development strategists and business communities who influence the policy of industrial development and its environmental sustainability.
Contents: About this publication -- Introduction -- Part I: Summary tables -- Part II: Country tables.
Description based on print record.
Keywords: Mines and mineral resources -- Statistics; Electronic books